ATP and Adenosine Metabolism in Cancer: Exploitation for Therapeutic Gain - Yegutkin Gennady G; Boison Detlev (United States, 2022)
Adenosine is an evolutionary ancient metabolic regulator linking energy state to physiologic processes, including immunomodulation and cell proliferation. Tumors create an adenosine-rich immunosuppressive microenvironment through the increased release of ATP from dying and stressed cells and its ectoenzymatic conversion into adenosine. Therefore, the adenosine pathway becomes an important therapeutic target to improve the effectiveness of immune therapies. Prior research has focused largely on the two major ectonucleotidases, ectonucleoside triphosphate diphosphohydrolase 1/cluster of differentiation (CD)39 and ecto-5'-nucleotidase/CD73, which catalyze the breakdown of extracellular ATP into adenosine, and on the subsequent activation of different subtypes of adenosine receptors with mixed findings of antitumor and protumor effects. New findings, needed for more effective therapeutic approaches, require consideration of redundant pathways controlling intratumoral adenosine levels, including the alternative NAD-inactivating pathway through the CD38-ectonucleotide pyrophosphatase phosphodiesterase (ENPP)1-CD73 axis, the counteracting ATP-regenerating ectoenzymatic pathway, and cellular adenosine uptake and its phosphorylation by adenosine kinase. This review provides a holistic view of extracellular and intracellular adenosine metabolism as an integrated complex network and summarizes recent data on the underlying mechanisms through which adenosine and its precursors ATP and ADP control cancer immunosurveillance, tumor angiogenesis, lymphangiogenesis, cancer-associated thrombosis, blood flow, and tumor perfusion. Special attention is given to differences and commonalities in the purinome of different cancers, heterogeneity of the tumor microenvironment, subcellular compartmentalization of the adenosine system, and novel roles of purine-converting enzymes as targets for cancer therapy. SIGNIFICANCE STATEMENT: The discovery of the role of adenosine as immune checkpoint regulator in cancer has led to the development of novel therapeutic strategies targeting extracellular adenosine metabolism and signaling in multiple clinical trials and preclinical models. Here we identify major gaps in knowledge that need to be filled to improve the therapeutic gain from agents targeting key components of the adenosine metabolic network and, on this basis, provide a holistic view of the cancer purinome as a complex and integrated network.